Showcasing the Great Experiment: Cultural Diplomacy and Western Visitors to the Soviet Union, 1921–1941 - Niergarth, Kirk (Labour / Le Travail, 2014)
This article reviews the book, "Showcasing the Great Experiment: Cultural Diplomacy and Western Visitors to the Soviet Union, 1921–1941," by Michael David-Fox.